Indigenous Production Technology of Latkan Practiced in Narsindi District - Alam, MS; Miah, MG; Hasan, MK (Journal of Agriculture & Rural Development, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> DOI = 10.3329/jard.v5i1.1475 J Agric Rural Dev 5(1&2), 173-175, June 2007